Specifications for plant protection products - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Manual on the development and use of FAO specifications for plant protection products 1995 138pp ISBN 925 103638 1